The effect of speed and influence of individual muscles on hamstring mechanics during the swing phase of sprinting - Chumanov, E. S.; Heiderscheit, B. C.; Thelen, D. G. (Journal of Biomechanics, 2007)
The purpose of this study was to characterize the effect of speed and influence of individual muscles on hamstring stretch, loading, and work during the swing phase of sprinting. We measured three-dimensional kinematics and electromyography (EMG) activities of 19 athletes sprinting on a treadmill at speeds ranging from 80% to 100% of maximum speed. We then generated muscle-actuated forward dynamic simulations of swing and double float phases of the sprinting gait cycle. Simulated lower extremity joint angles and model predicted excitations were similar to measured quantities. Swing phase simulations were used to characterize the effects of speed on the peak stretch, maximum force, and negative work of the biceps femoris long head (BF), the most often injured hamstring muscle. Perturbations of the double float simulations were used to assess the influence of individual muscles on BF stretch.